Prevalence of ear infections in first year children of primary schools in a western Ugandan community - Kisembo P; Mugwanya F; Atumanya P; Othin M; Oworinawe R; Kagimu B; Kisakye A; Bagambe F (African journal of biomedical research, 2018)
Ear infections in the United Kingdom were reported at a prevalence of 90% in children aged 0-6 years peaking at six years, the commonest age for Ugandan children to start primary school. This study was done to determine prevalence of ear infections in primary one children in Mbarara district, identify commonest ear infections, the causative pathogens isolated and their antibiograms and comparing the prevalence of ear infection in urban and rural schools. A cross sectional study was carried out among three urban day schools and three rural day schools randomly chosen in Mbarara district. History was taken using a data collection form and examinations were done using an otoscope. All pus swabs from infected ears were inoculated on Blood agar, Chocolate agar, MacConkey Agar plates before smears for Gram staining were made. Identification of the pathogen was through biochemical tests and API system. Sensitivity tests to antibiotics were set on Mueller Hinton Agar using the disc diffusion technique of Kirby-Bauer. Otoscopy was done on 600 children, 8.0 %( 48) showed signs of ear infections. The commonest ear infection was otitis externa. Staphylococcus aureus species showed the highest prevalence with 75% (6). Staphylococcus aureus species showed 100% sensitivity to gentamicin, 80% sensitivity to ciproflaxin. Serratia marcencens also showed 100% sensitivity to ciproflaxin, The prevalence of ear infection was 8.0% among children in primary one in Mbarara district in a cross sectional Study.
Keywords: Ear infections; Primary school children; Antibiograms; South-west Uganda